Uczniowie cudzoziemscy w polskiej szkole – między integracją a marginalizacją - Januszewska, Edyta (Wydawnictwo Naukowe UAM, 2017)
The text concerns the situation of culturally different children in the environment of Polish schools. The first part presents selected regulations of international and domestic law referring to the education of foreign children. The second and third parts present the challenges of a multicultural Polish school; the cited statistical data illustrate the insignificant presence of foreign children in Polish schools. The text is based on the analysis of academic literature, reports from non-governmental organizations and various legal regulations referring to the functioning of migrant children in Poland. It also draws on fragments of the Author’s research conducted within the project ‘A culturally different child in Poland. A pedagogical study of “rooting”’, realised in the years 2011–2014 in the Mazovian voivodeship and the capital city of Warsaw.
Foreign Students in Polish Schools – Between Integration and Marginalization
Keywords: foreign students in Poland; right to education and compulsory education in selected acts of international and domestic law; statistical data on refugee children in Polish schools